Coalition politics in Central Eastern Europe governing in times of crisis - Bergman, Torbjörn 1957-; Ilonszki, Gabriella 1953-; Hellström, Johan 1976- (Routledge Taylor & Francis Group, 2024)
"This insightful book brings the study of coalitions and coalition governance in Central and Eastern European democracies up to date, with an analytical focus framed by difficult economic and social periods, such as the end of the economic crisis and the Coronavirus pandemic. This book will be of key interest to scholars and students of coalition politics, representative democracy, governance, political parties, European Union politics, East and Central European politics, and comparative politics"--
Keywords: Geschichte 1990-; Koalition; Osteuropa; Coalition governments / Europe, Central; Coalition governments / Europe, Eastern; Europe, Central / Politics and government / 1989-; Europe, Eastern / Politics and government / 1989-; Coalition governments; Politics and government; Central Europe; Eastern Europe; Since 1989; Aufsatzsammlung